The blind side of international investment law and policy: The need for investor-state conflict-management mechanisms fostering investment retention and expansion - Roberto Echandi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
Most countries strive to attract FDI, yet around one fourth of all FDI projects established in developing countries are discontinued due to unresolved investor-state conflicts that never reach the limelight of investor-state litigation. This Perspective introduces investor-state conflict-management mechanisms (CMMs) to facilitate investment permanence and expansion in host countries.
Keywords: 330